Employing the R2L methodology with translanguaging to support written production of the daily routine genre - Mendoza Godoy, Diego (Árboles y Rizomas, 2024)
This paper presents a pedagogical action research project conducted at a Chilean tertiary education institution which explores the teaching of written production in English as a foreign language (EFL). It examines the application of the Reading to Learn (R2L) methodology, based on the principles of Systemic Functional Linguistics (SFL), which provides systematic support for students to produce a variety of genres. The intervention consists of two phases in which the R2L methodology is employed for teaching the daily routine genre. In this study, the R2L methodology focuses on allowing students to develop the necessary linguistic resources for the production of both first-person singular and third-person singular daily routines. To facilitate this, the intervention utilizes two teaching tools: the steps of the R2L methodology and translanguaging. The findings reveal that the R2L methodology alongside translanguaging significantly improved students’ ability to produce well-structured and purposeful daily routines, incorporating a range of linguistic choices.